Infants’ sensitivity to phonotactic regularities related to perceptually low-salient fricatives: a cross-linguistic study - Piot, Leonardo; Nazzi, Thierry; Boll-Avetisyan, Natalie (Frontiers in Psychology, 2024)
Introduction Infants’ sensitivity to language-specific phonotactic regularities emerges between 6- and 9- months of age, and this sensitivity has been shown to impact other early processes such as wordform segmentation and word learning. However, the acquisition of phonotactic regularities involving perceptually low-salient phonemes (i.e., phoneme contrasts that are hard to discriminate at an early age), has rarely been studied and prior results show mixed findings. Here, we aimed to further assess infants’ acquisition of such regularities, by focusing on the low-salient contrast of /s/- and /ʃ/-initial consonant clusters. Methods Using the headturn preference procedure, we assessed whether French- and German-learning 9-month-old infants are sensitive to language-specific regularities varying in frequency within and between the two languages (i.e., /st/ and /sp/ frequent in French, but infrequent in German, /ʃt/ and /ʃp/ frequent in German, but infrequent in French). Results French-learning infants preferred the frequent over the infrequent phonotactic regularities, but the results for the German-learning infants were less clear. Discussion These results suggest crosslinguistic acquisition patterns, although an exploratory direct comparison of the French- and German-learning groups was inconclusive, possibly linked to low statistical power to detect such differences. Nevertheless, our findings suggest that infants’ early phonotactic sensitivities extend to regularities involving perceptually low-salient phoneme contrasts at 9 months, and highlight the importance of conducting cross-linguistic research on such language-specific processes.